A satellite-derived baseline of photosynthetic life across Antarctica - Walshaw, Charlotte V.; Gray, Andrew; Fretwell, Peter T.; Convey, Peter; Davey, Matthew P.; Johnson, Joanne S.; Colesie, Claudia (Nature Geoscience, 2024)
Terrestrial vegetation communities across Antarctica are characteristically sparse, presenting a challenge for mapping their occurrence using remote sensing at the continent scale. At present there is no continent-wide baseline record of Antarctic vegetation, and large-scale area estimates remain unquantified. With local vegetation distribution shifts now apparent and further predicted in response to environmental change across Antarctica, it is critical to establish a baseline to document these changes. Here we present a 10 m-resolution map of photosynthetic life in terrestrial and cryospheric habitats across the entire Antarctic continent, maritime archipelagos and islands south of 60° S. Using Sentinel-2 imagery (2017–2023) and spectral indices, we detected terrestrial green vegetation (vascular plants, bryophytes, green algae) and lichens across ice-free areas, and cryospheric green snow algae across coastal snowpacks. The detected vegetation occupies a total area of 44.2 km2, with over half contained in the South Shetland Islands, altogether contributing just 0.12% of the total ice-free area included in the analysis. Due to methodological constraints, dark-coloured lichens and cyanobacterial mats were excluded from the study. This vegetation map improves the geospatial data available for vegetation across Antarctica, and provides a tool for future conservation planning and large-scale biogeographic assessments.
Keywords: Antarktis; alger; biodiversitet; botanikk; lav; planter

Nitrogen isotope fractionation explains the 15N enrichment of Antarctic cryptogams by volatilized ammonia from penguin and seal colonies - Bokhorst, Stef; van Logtestijn, Richard; Convey, Peter; Aerts, Rien (Polar Research, 2019)
Vegetation near bird and seal rookeries typically has high δ15N signatures and these high values are linked to the enriched δ15N values of rookery soils. However, Antarctic cryptogams are mostly dependent on atmospheric ammonia (NH3) and volatized NH3 from rookeries is severely depleted in δ15N-NH3. So there is an apparent discrepancy between the isotopically depleted source (NH3) and δ15N-enriched vegetation. In this article, we aim to resolve this discrepancy to better understand the mechanisms and processes involved in isotopic changes during nitrogen transfer between Antarctic marine and terrestrial ecosystems. Under laboratory conditions, we quantified whether volatized NH3 affects the isotopic signature of cryptogams. NH3 volatilizing from penguin guano and elephant seal dung was depleted (44–49‰) in δ15N when captured on acidified filters, compared to the source itself. Cryptogams exposed to the volatized NH3 were enriched (18.8–23.9‰) in δ15N. The moss Andreaea regularis gained more nitrogen (0.9%) than the lichen Usnea antarctica (0.4%) from volatilized NH3, indicating a potential difference in atmospheric NH3 acquisition that is consistent with existing field differences in nitrogen concentrations and δ15N between mosses and lichens in general. This study clarifies the δ15N enrichment of cryptogams resulting from one of the most important nitrogen pathways for Antarctic vegetation.
Keywords: Antarktis; fugler; kjemiske analyser; kryptogamer; lav; moser; planter; seler; økologi

Psoroma antarcticum, a new lichen species from Antarctica and neighbouring areas - Park, Chae Haeng; Hong, Soon Gyu; Elvebakk, Arve (Polar Biology, 2018)
Keywords: Antarktis; biodiversitet; botanikk; lav; moser; planter

Description of plant communities on Half Moon Island, Antarctica - Schmitz, Daniela; Putzke, Jair; Pereira de Albuquerque, Margéli; Schünemann, Adriano Luis; Costa Beber Vieira, Frederico; de Carvalho Victoria, Filipe de Carvalho Victoria; Batista Pereira, Antônio (Polar Research, 2018)
During February–March of the austral summers of 2013/14 and 2014/2015, fieldwork was performed on Half Moon Island, South Shetland Archipelago, Antarctica, to evaluate the distribution and abundance of mosses and lichens, as well as to describe and map the plant communities there. The quadrat (20 × 20 cm) sampling method was employed in a phytosociological study that aimed to describe these communities. The area was mapped using an Astech Promark II® DGPS, yielding sub-metric precision after post-processing with software. The number of species totalled 38 bryophytes, 59 lichens, only one flowering plant (Deschampsia antarctica Desv.), and two macroscopic terrestrial algae. Five types of plant communities were identified on the island, as follows: (1) fruticose lichen and moss cushion, (2) moss carpet, (3) muscicolous lichen, (4) crustose lichen and (5) moss turf.
Keywords: Antarktis; botanikk; bryozoa; flora; fytososiologi; lav; moser; planter; økologi

Patterns of fungal–algal symbiont association in Usnea aurantiaco-atra reveal the succession of lichen–moss communities in Fildes Peninsula, Antarctica - Cao, Shunan; Peng, Fang; Zheng, Hongyuan; Liu, Chuanpeng; Zhou, Qiming (Polar Research, 2017)
Usnea aurantiaco-atra is the most widespread flora in Fildes Peninsula. There are two growth types of U. aurantiaco-atra: the erect form on rocks and the prostrate form associated with mosses. Phylogenetic analysis showed that individuals of the two growth forms share genotypes. Moreover, haploid disequilibrium testing indicated no significant genetic difference for the two growth forms when fungal and algal internal transcribed spacer rDNA were treated as two alleles of one lichen individual. The two growth forms of U. aurantiaco-atra appear to reflect different stages of lichen–moss community succession. A mode is proposed for demonstrating the occurrence of this succession.
Keywords: Antarktis; botanikk; flora; fylogenetikk; lav; moser; planter

Mapping lichen distribution on the Antarctic Peninsula using remote sensing, lichen spectra and photographic documentation by citizen scientists - Casanovas, Paula; Black, Martin; Fretwell, Peter; Convey, Peter (Polar Research, 2015)
On the Antarctic Peninsula, lichens are the most diverse botanical component of the terrestrial ecosystem. However, detailed information on the distribution of lichens on the Antarctic Peninsula region is scarce, and the data available exhibit significant heterogeneity in sampling frequency and effort. Satellite remote sensing, in particular the use of the Normalized Difference Vegetation Index (NDVI), has facilitated determination of vegetation richness and cover distribution in some remote and otherwise inaccessible environments. However, it is known that using NDVI for the detection of vegetation can overlook the presence of lichens even if their land cover is extensive. We tested the use of known spectra of lichens in a matched filtering technique for the detection and mapping of lichen-covered land from remote sensing imagery on the Antarctic Peninsula, using data on lichen presence collected by citizen scientists and other non-specialists as ground truthing. Our results confirm that the use of this approach allows for the detection of lichen flora on the Antarctic Peninsula, showing an improvement over the use of NDVI alone for the mapping of flora in this area. Keywords: Antarctica; NDVI; matched filtering; Landsat; remote sensing.
Keywords: Antarktis; botanikk; flora; lav; satellitt bilder; økosystemer

Characterization and mapping of plant communities at Hennequin Point, King George Island, Antarctica - Victoria, Filipe de C; de Albuquerque, Margéli P; Pereira, Antonio B; Simas, Felipe N B; Spielmann, Adriano A; Schaefer, Carlos E G R (Polar Research, 2013)
King George Island is the largest island and the principal area used for research bases in Antarctica. Argentina, Brazil, Chile, China, Poland, Russia, South Korea and Uruguay have permanent open bases on this island. Other countries have seasonal summer stations on different parts of this island, which demonstrates that human impact is strong on King George Island relative to other areas in the maritime and continental Antarctica. The objective of this work was to present a phytosociological approach for ice-free areas of Hennequin Point, eastern coast of Admiralty Bay, King George Island. The study started with the classification and description of the plant communities based primarily on phytosociological and biodiversity data. The area was mapped using an Astech Promark II® DGPS, yielding sub-metric precision after post-processing with software. The plant communities were described as follows: (1) lichen and moss cushion formation; (2) moss carpet formation; (3) fellfield formation; (4) grass and cushion chamaephyte formation; and (5) Deschampsia Antarctica–lichen formation. Characterizations and distributions of the plant communities are presented on a map at a scale of 1:5000. The plant communities found at Hennequin Point, in general, differ from those found in other areas of the Admiralty Bay region, probably because of the concentration of skua nests in the area and the relief singularities. We conclude by highlighting the importance of the study of plant species found in the ice-free areas of the Antarctic with respect to environmental monitoring and for evaluating global climate and environmental changes. Keywords: Plant communities mapping; lichens; mosses; flowering plants; Antarctic
Keywords: Antarktis; biodiversitet; fytososiologi; klimaendringer; lav; miljøendringer; moser; planter; plantesosiologi

Low genetic diversity in Antarctic populations of the lichenforming ascomycete Cetraria aculeata and its photobiont - Domaschke, Stephanie; Fernández-Mendoza, Fernando; Garcia, Miquel A; Martín, Maria P; Printzen, Christian (Polar Research, 2012)
Lichens, symbiotic associations of fungi (mycobionts) and green algae or cyanobacteria (photobionts), are poikilohydric organisms that are particularly well adapted to withstand adverse environmental conditions. Terrestrial ecosystems of the Antarctic are therefore largely dominated by lichens. The effects of global climate change are especially pronounced in the maritime Antarctic and it may be assumed that the lichen vegetation will profoundly change in the future. The genetic diversity of populations is closely correlated to their ability to adapt to changing environmental conditions and to their future evolutionary potential. In this study, we present evidence for low genetic diversity in Antarctic mycobiont and photobiont populations of the widespread lichen Cetraria aculeata. We compared between 110 and 219 DNA sequences from each of three gene loci for each symbiont. A total of 222 individuals from three Antarctic and nine antiboreal, temperate and Arctic populations were investigated. The mycobiont diversity is highest in Arctic populations, while the photobionts are most diverse in temperate regions. Photobiont diversity decreases significantly towards the Antarctic but less markedly towards the Arctic, indicating that ecological factors play a minor role in determining the diversity of Antarctic photobiont populations. Richness estimators calculated for the four geographical regions suggest that the low genetic diversity of Antarctic populations is not a sampling artefact. Cetraria aculeata appears to have diversified in the Arctic and subsequently expanded its range into the Southern Hemisphere. The reduced genetic diversity in the Antarctic is most likely due to founder effects during long-distance colonization. The environmental conditions of the Antarctic are among the most adverse on Earth and are generally characterized by low mean annual temperatures, high wind velocities, extreme drought and extended periods of darkness. The effects of global climate change are especially pronounced in parts of the Antarctic (Turner et al. 2005). Air temperature in the maritime Antarctic has steadily increased within the last years (Smith & Stammerjohn 1996; Turner et al. 2005). On the western Antarctic Peninsula a temperature increase of more than 2.5 K has been observed over the last 50 years. The overall effect of such a temperature increase on terrestrial Antarctic organisms could be beneficial. For example, glacial melting will increase the availability of terrestrial (page number not for citation purpose). Keywords Genetic diversity; lichens; Cetraria aculeata; Trebouxia jamesii; polar lichens; global change.
Keywords: Antarktis; alger; fotobiont; genetisk mangfold; klimaendringer; lav; sopper; økosystemer

Notes on two subantarctic pannariaceous lichens - Jørgensen, Per Magnus (Cryptogamie Mycologie, 2005)
It is shown by use of a newly discovered, old photo of the missing type that Siphulina orphnina (Hue) C. W. Dodge is identical with Pannaria caespitosa P. M. Jorg. The new combination Pannaria orphnina (Hue) R M. Jorg. is made, and the name neotypitied. Parmeliella austroshetlandica Sochting & Ovstedal is shown to be a species in the small subantarctic genus Peltularia R. Sant. (Coccocarpiaceae), and is transferred to that genus.
Keywords: Antarktis; biologi; botanikk; lav; planter

Additions and corrections to the Lichens of Antarctica and South Georgia - Øvstedal, Dag; Smith, Ronald I. Lewis (Cryptogamie, Mycologie, 2004)
The taxonomic listing given in Lichens of Antarctica and South Georgia (Øvstedal & Lewis Smith 2001) has been updated. 17 additional taxa of lichenised fungi are described, including several nomenclatural changes. 14 of these are considered as new records for the Antarctic and one is new to South Georgia. One is described as new to science.
Keywords: Antarktis; biogeografi; botanikk; lav; planter; taksonomi

Lichens of Antarctica and South Georgia : a guide to their identification and ecology - Øvstedal, Dag Olav; Smith, Ronald Lewis (Cambridge University Press, 2001)
Keywords: Antarktis; botanikk; lav; planter

A new species of Parmelia (lichenized Ascomycotina) from the Antarctic - Øvstedal, Dag Olav; Elix, John A.; Smith, Ronald I. Lewis (Mycotaxon, 1998)
A new species of Parmelia (lichenized Ascomycotina) from the Antarctic. Parmelia lindsayana Ovstedal & Elix from Signy Island (South Orkney Islands) is described as new. This species resembles P. protosulcata Hale and P. cunninghamii Crombie, but differs in morphological details and in containing usnic, alpha-collatolic and alectoronic acids.
Keywords: Antarktis; Sør-Orknøyene; botanikk; lav; planter

Caloplaca Lewis-Smithii, a new lichen species from continental Antarctica - Søchting, Ulrik; Øvstedal, Dag Olav (Mycotaxon, 1998)
A new muscicolous lichen species, Caloplaca lewis-smithii Søchting & Øvst., is described from Victoria Land, continental Antarctica. It is characterized by a grey to blackish brown microlobate thallus and a blackish apothecial disk with a white pruinose thalline margin.
Keywords: Antarktis; botanikk; lav; planter; sopper

Responses of terrestrial plants and invertebrates to environmental change at high latitudes - Callaghan, Terry V.; Sonesson, Mats; Sømme, Lauritz; Walton, D. W. H.; Christensen, T.; Block, W. C.; Drewry, D. J.; Laws, Richard Maitland; Pyle, John Adrian (Philosophical Transactions of the Royal Society of London. Series B: Biological Sciences, 1997)
Many invertebrates show flexibility in their life cycles and are likely to respond to changes in climate as they have in the past. However, changes in temperature and photoperiod may disturb the life cycles of some existing polar invertebrates while continuing to constrain the polewards migration of more temperate species. Higher plants are likely to have higher productivity as temperatures and atmospheric CO2 levels increase but this productivity will be reduced by exposure to increasing UV-B radiation. Higher plants migrate more slowly than the rate at which climate is predicted to change and many species will be trapped in supra-optimal climates. Both mosses and lichens can migrate faster than higher plants, propagules of non-polar species already reaching the Antarctic, but they have fewer mechanisms of responding to changing environments. Polar vegetation and ecosystems provide feedback to the climate system: positive feedbacks are associated with decreases in reflectivity and increased carbon emissions from warm ing soils. In the Antarctic, feedback and responses to environmental change will be smaller than in the Arctic because of the less responsive cryptogams which dominate the Antarctic, the paucity of Antarctic soils, and geographical barriers to plant and invertebrate migrations.
Keywords: Antarktis; biologi; botanikk; klimaendringer; lav; moser; virvelløse dyr

Cold resistance and metabolic activity of lichens below 0°C - Kappen, Ludger; Schroeter, Burkhard; Scheidegger, Christoph; Sommerkorn, Martin; Hestmark, Geir (Proceedings of the F3.1, F3.4, F2.4 and F3.8 Symposia of COSPAR Scientific Commission F, 1996)
Laboratory measurements show that lichens are extremely tolerant of freezing stress and of low-temperature exposure. Metabolic activity recovered quickly after severe and extended cold treatment. Experimental results demonstrate also that CO2 exchange is already active at around −20°C. The psychrophilic character of polar lichen species is demonstrated by optimum temperatures for net photosynthesis between 0 and 15°C. In situ measurements show that lichens begin photosynthesizing below 0°C if the dry thalli receive fresh snow. The lowest temperature measured in active lichens was −17°C at a continental Antarctic site. The fine structure and the hydration state of photobiont and mycobiont cells were studied by low-temperature scanning electron microscopy (LTSEM) of frozen hydrated specimens. Water potentials of the frozen system are in the range of or even higher than those allowing dry lichens to start photosynthesis by water vapor uptake at +10°C. The great success of lichens in polar and high alpine regions gives evidence of their physiological adaptation to low temperatures. In general lichens are able to persist through glacial periods, but extended snow cover and glaciation are limiting factors.
Keywords: Antarktis; botanikk; frostresistens; lav; planter; polarområdene

Two further bipolar lichens - Øvstedal, Dag Olav; Gremmen, Niek J M (Graphis scripta, 1995)
Keywords: Antarktis; botanikk; lav; planter

Solorina Spongiosa in Antarctica: An Extremely Disjunct Bipolar Lichen - Smith, R. I. Lewis; Øvstedal, Dag Olav (The Lichenologist, 1994)
The bipolar foliose lichen Solorina spongiosa (Sm.) Anzi is reported from James Ross Island, Antarctica, where it grows on moss. This is only the third known occurrence of this lichen from the Southern Hemisphere, the other localities being in Tierra del Fuego and New Zealand. Its morphology resembles that of the New Zealand population and arctic-alpine populations from the Northern Hemisphere, although there are some differences in apothecial and spore size. As elsewhere, it occupies base-rich habitats colonized by predominantly calcicolous mosses and lichens.
Keywords: Antarktis; botanikk; lav; moser; planter

Pertusaria signyae (Lichenes), a new species from the Antarctic - Øvstedal, Dag Olav; Smith, Ronald I Lewis (Nova Hedwigia, 1992)
A saxicolous Pertusaria species is described as new to science: P. signyae Ovst. from South Orkney Islands. It has an isidiate thallus, subglobose fertile verrucae with poriform apothecia, and contains 2'-0-methylperlatolic acid.
Keywords: Antarktis; Sør-Orknøyene; botanikk; lav; planter

Contributions to the Caloplaca flora of the western Antarctic region - Søchting, Ulrik; Øvstedal, Dag Olav (Nordic Journal of Botany, 1992)
Fourteen species of the lichen genus Caloplaca are recorded from the western Antarctic region and described morphologically and anatomically, viz.: C. ammiospila, C. approximata, C. athallina, C. cirrochrooides, C. citrina, C. isidioclada, C. lucens, C. millegrana, C. regalis, C. sublobulata, C. tenuis, C. aff. anchon-phoeniceon. Type specimens of critical species have been studied. A key is provided to the species. Caloplaca ammiospila and C. approximata are reported as new to the Antarctic region.
Keywords: Antarktis; botanikk; lav; planter

Eine neue Gyalecta-Art aus der Antarctis: G. pezizoides sp. n. (lichensierte Fungi, Gyalectaceae) - Vezda, A.; Øvstedal, Dag Olav; Smith, Ronald I Lewis (Nova Hedwigia, 1992)
A new species of the genus Gyalecta, G. pezizoides sp. n. (lichenized Fungi, Gyalectaceae), is described and illustrated. This new species is taxonomically near to the holarctic Gyalecta peziza (Mont.) Anzi.
Keywords: Antarktis; botanikk; lav; planter

The lichen genus Stereocaulon in Antarctica and South Georgia - Smith, Ronald I Lewis; Øvstedal, Dag Olav (Polar Biology, 1991)
Six species of Stereocaulon and one unnamed taxon (close to S. glabrum) are reported from South Georgia, the maritime Antarctic islands and Antarctic Peninsula. S. caespitosum is new to the western sub-Antarctic. Variations in morphology and secondary chemistry are provided, and the ecology and geographical distribution in the sub-Antarctic and Antarctic biomes are given for each taxon.
Keywords: Antarktis; botanikk; lav; planter

Microclimates and water budget of algae, lichens and a moss on some nunataks in Queen Maud Land - Gjessing, Yngvar; Øvstedal, Dag Olav (International Journal of Biometeorology, 1989)
Keywords: Dronning Maud Land; NARE 1984/85; alger; biologi; lav; mikroklima; moser; planter

Muscicolous Lepraria species and other leprarioid lichens in the Antarctic - Botnen, Astri; Øvstedal, Dag Olav (Polar Research, 1988)
Keywords: Dronning Maud Land; botanikk; forskning; lav; planter

Cladonia galindezii, a new Antarctic lichen species - Øvstedal, Dag Olav (Cryptogamie, Bryologieet Lichénologie, 1988)
Keywords: Antarktis; botanikk; lav; planter

On the variation of Ochrolechia parella in the western Antarctic and Subantarctic area - Øvstedal, Dag Olav (Polarforschung, 1988)
Keywords: Antarktis; botanikk; lav; planter

Phytogeographical relations of the cryptogamic flora of Bouvetøya - Engelskjøn, Torstein; Jørgensen, Per Magnus (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; ekspedisjoner; lav

Macrolichens of Bouvetøya - Jørgensen, Per Magnus (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; lav

Crustose lichens of Bouvetøya - Øvstedal, Dag Olav (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; lav

Lichens and lichen parasites from the British-Swedish-Norwegian antarctic expedition 1949-52 to Dronning Maud Land - Øvstedal, Dag Olav (Cryptogamie: bryologie, lichenologie, 1986)
Keywords: Dronning Maud Land; botanikk; ekspedisjoner; lav; parasitter; planter

Lichencolous ascomycetes from Bouvetøya - Øvstedal, Dag Olav; Hawksworth, David L (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; lav

Some lichens from HU Sverdrup Mountains, Dronning Maud Land, Antarctis - Øvstedal, Dag Olav (Nova Hedwigia: Zeitschrift fur Kryptogamenkunde, 1983)
Keywords: Dronning Maud Land; botanikk; lav; planter

Some lichens from Vestfjella, Dronning Mauds Land, Antarctis - Øvstedal, Dag Olav (Cryptogamie. Bryologie, lichénologie, 1983)
Keywords: Dronning Maud Land; botanikk; lav; planter

A new Pannaria species from the Antarctic - Øvstedal, Dag Olav; Smith, Ronald Lewis (Cryptogamie, Bryologie, Lichenologie, 1983)
Pannaria austro-orcadensis Ovst., sp.nov., from the northern maritime Antarctic, is characterized by its purple-brown lobulate thallus, brown apothecia smooth spores and no secondary products. It grows on moist gravelly soil and bryophytes.
Keywords: Dronning Maud Land; botanikk; lav; planter

Lichens from Vestfjella, Dronning Maud Land - Lindsay, Denis Christopher (Norsk Polarinstitutt, 1972)
Keywords: Dronning Maud Land; botanikk; lav; planter